No journey too far [large type] - Turansky, Carrie (Turansky, Carrie. McAlister family, 2021)
"In 1909, Grace McAlister set sail for Canada as one of the thousands of British Home Children taken from their families and their homeland. Though she was fortunate enough to be adopted by wealthy parents, the secrets of her past were kept hidden for ten years until someone from her long-buried childhood arrives on her doorstep. With this new connection to her birth family, will she be brave enough to leave her sheltered life in Toronto and uncover the truth? After enduring hardship as an indentured British Home Child, Garth McAlister left Canada to serve in World War I. His sweetheart, Emma Lafferty, promised to wait for his return, but after three long years apart, her letters suddenly stopped. When Garth arrives home from the war to unexpected news, he is determined to return to Canada once more on a daunting mission to find the two women he refuses to abandon-- his long-lost sister and his mysteriously missing sweetheart"--